Implications of Legal Positivism of the Promotion of Children's Rights on National Law - TYESTA, Lita A.L.W.; SARASWATI, Retno; ARIF, Faisal (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).36, 2020)
This article discusses the influence of positivism in the development of legal science, especially in the development of Indonesian law. Through the positivism which was introduced by August Comte, the study aims to analyze the legal positivism as a strategic-political form that is needed in terms of promoting children's rights. As a result, positivism can not only be used as a medium used to help the modern process: the law there can also be used as a means to provide legal protection for the people’s, especially for the protection of children's rights.